If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -24 = 10x Reorder the terms: -24 + 9x = 10x Solving -24 + 9x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -24 + 9x + -10x = 10x + -10x Combine like terms: 9x + -10x = -1x -24 + -1x = 10x + -10x Combine like terms: 10x + -10x = 0 -24 + -1x = 0 Add '24' to each side of the equation. -24 + 24 + -1x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -1x = 0 + 24 -1x = 0 + 24 Combine like terms: 0 + 24 = 24 -1x = 24 Divide each side by '-1'. x = -24 Simplifying x = -24
| (9x+8)(8+x)=(x+5)(9x+8) | | 142+x=3x+64 | | 10+6/2 | | 20x-22y=58 | | 5/3p^2-3/p | | (x+5)(x-5)=(x+1)(x+3)+12 | | 4/20(2x-15)+12/20x=45/20 | | 4x^1/4-17x^1/2+4=0 | | 4=n+11 | | 3x-4=x+9 | | 2(4-3x)+12=7x-5(2x-7) | | -3(8k-3)=-17+2k | | 7(x-1)+3= | | 2(x-2)/3+5x=10 | | 3w-5+3w-5= | | 2(x-2)/5+5x=10 | | 240/275 | | 4x-(x^2)=0 | | 55x=1 | | 11x^2-28x-15=0 | | 25a^2+60ab+36b^2-64=0 | | 3x/5-0.5+1.9 | | (15/1)/(-3/4) | | x=180-(90-x)-4 | | 6(x+2)+10x=8x+3(x-9) | | x=180-((90-x)-4) | | 15/1/-3/4 | | x/6-x+3/5=1 | | 6x+9=9x+3 | | r+5/3=-6 | | M-12=18 | | .75y-5=-.5y+4 |